Re-examination of species limits in Aspergillus section Flavipedes using advanced species delimitation methods and description of four new species - Sklenář, F; Jurjević, Ž; Houbraken, J; Kolařík, M; Arendrup, M C; Jørgensen, K M; Siqueira, J P Z; Gené, J; Yaguchi, T; Ezekiel, C N; Silva Pereira, C; Hubka, V (Studies in mycology, 2021)
Since the last revision in 2015, the taxonomy of section Flavipedes evolved rapidly along with the availability of new species delimitation techniques. This study aims to re-evaluate the species boundaries of section Flavipedes members using modern delimitation methods applied to an extended set of strains (n = 90) collected from various environments. The analysis used DNA sequences of three house-keeping genes (benA, CaM, RPB2) and consisted of two steps: application of several single-locus (GMYC, bGMYC, PTP, bPTP) and multi-locus (STACEY) species delimitation methods to sort the isolates into putative species, which were subsequently validated using DELINEATE software that was applied for the first time in fungal taxonomy. As a result, four new species are introduced, i.e. A. alboluteus, A. alboviridis, A. inusitatus and A. lanuginosus, and A. capensis is synonymized with A. iizukae. Phenotypic analyses were performed for the new species and their relatives, and the results showed that the growth parameters at different temperatures and colonies characteristics were useful for differentiation of these taxa. The revised section harbors 18 species, most of them are known from soil. However, the most common species from the section are ecologically diverse, occurring in the indoor environment (six species), clinical samples (five species), food and feed (four species), droppings (four species) and other less common substrates/environments. Due to the occurrence of section Flavipedes species in the clinical material/hospital environment, we also evaluated the susceptibility of 67 strains to six antifungals (amphotericin B, itraconazole, posaconazole, voriconazole, isavuconazole, terbinafine) using the reference EUCAST method. These results showed some potentially clinically relevant differences in susceptibility between species. For example, MICs higher than those observed for A. fumigatus wild-type were found for both triazoles and amphotericin B for A. ardalensis, A. iizukae, and A. spelaeus whereas A. lanuginosus, A. luppiae, A. movilensis, A. neoflavipes, A. olivimuriae and A. suttoniae were comparable to or more susceptible as A. fumigatus. Finally, terbinafine was in vitro active against all species except A. alboviridis.
Keywords: Aspergillus alboviridis J.P.Z. Siqueira, Gené, F. Sklenar & Hubka; Antifungal susceptibility testing; Multigene phylogeny; Soil-borne fungi; Aspergillus flavipes; Indoor fungi; Clinical fungi; Species delimitation; Aspergillus inusitatus F. Sklenar, C. Silva Pereira, Houbraken & Hubka; Aspergillus alboluteus F. Sklenar, Jurjević, Ezekiel, Houbraken & Hubka; Aspergillus lanuginosus F. Sklenar & Hubka